MindHike, a Digital Coaching Application to Promote Self-Control: Rationale, Content, and Study Protocol - Allemand, Mathias; Keller, Lara; Gmür, Benjamin; Gehriger, Victoria; Oberholzer, Timon; Stieger, Mirjam (Frontiers in Psychiatry, 2020)
This protocol describes a study that will test the effectiveness of a seven-week non-clinical digital coaching intervention to promote self-control. The goal of the coaching is to support and guide people who are willing and motivated to improve their self-control with the help of the smartphone application MindHike. The coaching is based on a process model of self-control and aims to target five groups of self-control strategies. The goal of the study is to examine the effectiveness of the digital coaching intervention. A single-arm study design with pretest, posttest and two-month follow-up assessments and process assessments will be used to evaluate the seven-week digital coaching intervention. The digital coaching includes 49 daily lessons that are organized along seven weekly core themes. Study participants will be at least 150 adults aged 18 years and older who are willing and motivated to improve their self-control using the MindHike application. This is the first study testing the effectiveness of a digital coaching intervention to promote self-control. Given that this approach proves effective, it could be easily implemented in various non-clinical settings such as education, health, relationship, and work, and in clinical settings. Due to its digital low-threshold character, it could also reach large numbers of people.